Penerapan Teknologi Penabur Pupuk Padat Sederhana Berbahan Dasar Barang Bekas di Kampung Kalicaah, Desa Tanjung Jaya, Kecamatan Panimbang - Ulfi Jefri; Muhammad Aldi Alfikhar; Muhamad Irfan; Nur Cholis Majid; Mohammad Rifki Riadi; Erwin Apdino Manullang (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This community service program was implemented to address the needs of farmers in Kalicaah Village, Tanjung Jaya Village, Panimbang District, for an affordable, simple, and user-friendly fertilizing tool. Traditionally, the application of solid fertilizer has been done manually, which not only leads to inefficiency but also significantly increases the physical workload of farmers. To overcome this issue, the program team designed a solid fertilizer spreader using appropriate technology, constructed from recycled materials such as PVC pipes and used water gallons. This innovation was aimed at creating a sustainable, low-cost solution for the local agricultural community. The program’s implementation involved several key activities, including identifying the farmers' challenges, conducting assembly training sessions, demonstrating the tool’s use, and running direct field trials in local farms. The results showed that the use of the newly developed fertilizer spreader led to a 45% reduction in the time spent applying fertilizer, which directly contributed to more efficient farming practices. Additionally, there was a significant reduction in physical complaints, particularly lower back pain, which had been a common issue due to the manual labor involved in fertilizing. The tool proved to be easy to construct, requiring minimal technical knowledge, and the farmers were able to adopt the technology independently. The high rate of adoption among farmers further emphasizes the tool’s potential for widespread use. The success of this program also suggests that this simple, affordable technology could be replicated in other agricultural regions, benefiting more communities by improving work efficiency, reducing physical strain, and fostering a sustainable approach to farming practices.